Turning consumers into partners: creating opportunities for business model innovation in retailing - Vi, Thi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Retail business in the developed markets has reached a tough time of competition, having been struggling to find a healthier way than massively reducing prices. Although innovation has been commonly considered a significant chance for business firms to overcome this challenge, the deployment of innovative marketing tactics or advanced technologies seems to gradually lose its weight in making retailers distinctive. As an attempt to deal with this problem, this study, instead, investigated into innovation from a modern approach on business models, focusing on consumers’ contributions when they are involved as the retailers’ partners. The purpose was to seek the opportunities created by these consumer partnerships for innovation of retailing business models. A theoretical framework depicting the influences of the consumer partnerships on the retailing business model innovation was built based on related studies. Qualitative research was applied in studying a specific case of the Prisma chain in Southwestern Finland – a big retailer which has developed a strong buyer-seller relationship. Data gathered from both primary and secondary sources were used to identify the partner roles of Prisma’s consumers; and the effects on the business model of this retailer. The findings revealed that the consumer partnerships have great impacts on retailing business models. Also, it is possible that these influences would trigger innovation taking place in business models, however rarely, unless retailers intentionally invest in consumer partnerships as well as plan to capture their generated value. The positive influences of consumer partnerships found in this study encourage retailers to have a new attitude towards business model innovation. As it is considered risky, getting consumers involved as business partners can be a solution. This study offered the framework as a guide for the retailers to evaluate their current consumer partnerships and to decide their focus for developing this relationship in a way that benefits business model innovation. Lastly, this study also contributed to the understanding of the relationship between consumer partnerships and retailing business model innovation; thus, it calls for further research to continue exploring this fruitful domain.